PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, KOMPENSASI DAN LINGKUNGAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA GURU DI MAN 2 SITUBONDO - Shofiah, Annur; Sari, Lita Permata; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2025)
The aim of this research is to analyze and test the influence of situational leadership style, compensation and work environment with work motivation as an intervening variable on teacher performance at MAN 2 Situbondo. The population of this research is ASN teachers at MAN 2 Situbondo. The analysis and testing method in this research is using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that situational leadership style has a significant positive effect on work motivation, Compensation has a positive but not significant effect on work motivation, Work environment has a positive but not significant effect on work motivation, Situational leadership style has a positive but not significant effect significant effect on teacher performance, Compensation has a positive but not significant effect on teacher performance, Work environment has a negative but not significant effect on teacher performance, Work motivation has a significant effect on teacher performance, Situational leadership style has a significant effect on teacher performance through work motivation, Compensation has a positive effect but not significant on performance through job satisfaction. The work environment has a positive but not significant effect on teacher performance through job satisfaction.